2023
DOI: 10.1523/jneurosci.0091-23.2023
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and Inhibition Delays within a Feedforward Inhibitory Pathway Modulate Cerebellar Purkinje Cell Output in Mice

Abstract: The cerebellar cortex computes sensorimotor information from many brain areas through a feedforward inhibitory (FFI) microcircuit between the input stage, the granule cell layer, and the output stage, the Purkinje cells (PC). While in other brain areas FFI underlies a precise excitation vs. inhibition temporal correlation, recent findings in the cerebellum highlighted more complex behaviors at the granule cell (GC) – molecular layer interneuron (MLI) – PC pathway. To dissect the temporal organization of this c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The analysis of the incoherent feedforward circuit was restricted to the interneuron frequency being equal to the presynaptic input frequency, and future work will relax this assumption. Another interesting direction of future work is to use these analytical models of feedforward circuits (both coherent and incoherent) to study several reported invivo examples of such circuits and understand their function in different neurological contexts [51]- [53].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the incoherent feedforward circuit was restricted to the interneuron frequency being equal to the presynaptic input frequency, and future work will relax this assumption. Another interesting direction of future work is to use these analytical models of feedforward circuits (both coherent and incoherent) to study several reported invivo examples of such circuits and understand their function in different neurological contexts [51]- [53].…”
Section: Discussionmentioning
confidence: 99%
“…The Fiala et al ( 1996 ) and Antunes and De Schutter ( 2012 ) synaptic models were used as basis for other synaptic models: the Steuber et al ( 2006 ) and Hepburn et al ( 2017 ) (in turn used for the Zamora Chimal and De Schutter, 2018 model), respectively. Finally, the Binda et al ( 2023 ) network model was based on the Grangeray-Vilmint et al ( 2018 ) model of the same type. Figure generated with BioRender.…”
Section: Discussionmentioning
confidence: 99%
“…In 2023, a network model based on the 2018 Grangeray-Vilmint model was used to investigate a temporal organization of the feedforward inhibitory microcircuit between GrCs, MLIs and PCs (Binda et al, 2023 ). Using ex vivo patch-clamp recordings of PCs and the Grangeray-Vilmint model, it was shown that the encoding of specific MF inputs by PCs can be aided by specific excitatory and inhibitory delays.…”
Section: Purkinje Cell Modelsmentioning
confidence: 99%